Metal ceramic material with white core black ring structure and preparation method thereof
Patent Information
- Application Number
- CN202610871926.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-06-16
- Publication Date
- 2026-08-11
AI Technical Summary
但是,通过大幅提升粘结相含量以提升金属陶瓷材料强度与韧性的方法,成本高昂,在实际工业生产中难以实施
(1)本发明提供了一种具有白芯黑环结构的金属陶瓷材料,a)通过添加10%~20%的Ti(C0.3,N0.7)和40%~50%的Ti(C0.5,N0.5),不仅可以避免过高的氮含量引起不可控的脱氮现象,还可以将Ti(C0.5,N0.5)作为芯环相形成的主要来源,增加硬质相与粘结相之间的整体润湿性,在确保材料硬度提高的同时兼顾其韧性;b)添加1%~4%的TaC、15%~30%的WC、0~10%的TiWC、2%~5%的Mo2C、0.2%~1.2%的Cr3C2,通过添加WC和Mo2C可以改善硬质相与粘结相之间的润湿性,且W、Mo元素与TiCN硬质相的固溶过程是形成灰环、白芯等结构的主要原因,即WC和Mo2C的添加对提高金属陶瓷材料的韧性起到了关键作用;通过添加TaC原料,其在氧反应后形成致密的氧化物薄膜,可以提高金属陶瓷的红硬性和抗热冲击性能;通过添加Cr3C2原料,可以抑制金属陶瓷材料中硬质相晶粒长大,从而提高其硬度和耐磨性;通过添加TiWC原料,以增加金属陶瓷材料中白芯相的占比,提高材料的韧性,同时该白芯相不通过烧结形成,因而能够在金属陶瓷材料组织中有效地控制白芯相的占比,从而减少由纯烧结产生白芯相的不确定性。本发明的金属陶瓷材料,其维氏硬度可达1641 HV30,断裂韧性可达11.23 MPa.m1/2,抗弯强度可达2648MPa。
Smart Images

Figure CN122542898A_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the field of metal ceramic materials technology, specifically relating to a metal ceramic material with a white core and black ring structure and its preparation method. Background Technology
[0002] Cutting tool materials encompass cemented carbide, cermets, and superhard materials. Among these, Ti(C,N)-based cermets are widely favored in the market due to their excellent comprehensive performance and relatively low cost, leading universities, research institutes, and enterprises to invest significant research resources in them. Ti(C,N)-based cermets typically consist of a metallic binder phase composed of Co, Ni, or Co+Ni, with TiC+TiN and Ti(C,N) as the binders. x N y ) or Ti(C x1 N y1 )+Ti(C x2 N y2 Ti(C,N)-based cermet materials use carbides such as WC, TaC, NbC, Mo2C, and Cr3C2 as additives to adjust properties and microstructure. These materials not only possess the high hardness of ceramics but also exhibit good strength and toughness. Their high-temperature wear resistance, oxidation resistance, and red hardness are significantly superior to cemented carbide materials. Furthermore, they have weak affinity for materials such as cast iron, steel, and copper alloys, making them less prone to tool sticking during cutting. This makes them the preferred material for manufacturing hot-working molds, high-speed, high-efficiency dry cutting tools, high-temperature wear-resistant and corrosion-resistant parts, and mechanical seal rings.
[0003] Nitrogen (N) is typically introduced into Ti(C,N)-based cermet materials in the form of TiN or Ti(C,N), and its influence on these materials is significant. Within a certain range, as the N content increases, the stability of Ti(C,N) increases, the number of undissolved Ti(C,N) grains in the microstructure increases, thus increasing the proportion of the black core structure, decreasing the thickness of the gray ring, and gradually refining the size of the hard phase, thereby increasing hardness and toughness. On the other hand, with the increase of N content, the content of elements such as Mo, W, Ta, and Nb precipitated during the formation of the core-ring structure in the binder phase decreases, resulting in an increase in the lattice constant of the binder phase, achieving a certain degree of solid solution strengthening. However, the N content cannot be continuously increased. When its content is too high, denitrification inevitably occurs in Ti(C,N)-based cermets during sintering, leading to a large number of pores in the microstructure and a sharp deterioration in mechanical properties. Therefore, although Ti(C,N)-based cermet materials with high nitrogen content have the above-mentioned excellent performance indicators, in actual industrial production, not only must the setting of high nitrogen content be considered, but also the principles of sintering process formulation must be clarified, and its mass production is still very difficult.
[0004] It is noteworthy that existing patent reports on mass-producible high-nitrogen-content Ti(C,N)-based cermet materials are very limited. For example, Chinese patent document CN202010013582.2 discloses a nanoparticle interface-reinforced high-nitrogen-content Ti(C,N)-based cermet material and its preparation method, the composition and content of the raw materials for preparation are as follows: (MoTi)(C x N 1-x 0~20wt%, WCR: 0~25wt%, ZrNbC: 0~5wt%, ZrNbHfC: 0~5wt%, TiC nanopowder: 0~10wt%, TiN nanopowder: 0~10wt%, Co+Ni: 6~20wt%, carbon powder: 0.35~1.5wt%, (TiWTa)(C x N 1-x ): 0~25wt%, (TiWNb)(C x N 1-x ): 0~25wt%, balance is Ti(C) x N 1-x (where 0.4≤x≤0.5). Unfortunately, on the one hand, the patent document does not disclose the specific mechanical property parameters of the invented material, which is insufficient to demonstrate that the invented material possesses excellent mechanical or machinability; on the other hand, the material uses a large amount of nanopowder raw materials and various high-entropy alloy powder raw materials, resulting in high preparation costs and making it difficult to demonstrate the low-cost advantage of metal-ceramic materials. Therefore, it is necessary to study a high-nitrogen metal-ceramic material with lower preparation costs.
[0005] Currently, research on Ti(C,N)-based cermet materials tends to focus on the use of high-carbon TiCN raw materials. For example, Chinese patent document CN202110250169.2 discloses a mixed-crystal Ti(C,N)-based cermet material and its preparation method, wherein the composition and content of the raw materials are as follows: Co+Ni, 14%~25%; Ti(C 0.5 N 0.5 ) and Ti(C 0.7 N 0.3 ), 40%–60%, Ti(C 0.5 N 0.5 ) / Ti(C 0.7 N 0.3 The concentration of TiCN in this preparation method is 0.6-1 μm; additives include (Ti,W)C solid solution, WC, TaC, NbC, Mo, Mo2C, Cr2C3, and VC, ranging from 15% to 46%. 0.7 N 0.3The main component is Ti(C), with a Fisher particle size of 1.4–2.0 μm added. 0.5 N 0.5 Increasing the overall carbon content of the material reduces the N / C ratio in TiCN, thereby decreasing the activity of N and reducing porosity formation in the cermet. However, since C has a stronger chemical affinity for elements such as W, Mo, and Ta than N does, high-nitrogen TiCN raw materials are more stable during sintering than high-carbon TiCN raw materials, and are less prone to diffusion and agglomeration, thus refining the cermet grains, provided that denitrification reactions during sintering are effectively suppressed. Furthermore, the strength and toughness of this mixed-crystal Ti(C,N)-based cermet material are significantly improved, mainly due to the use of a high binder phase. Specifically, compared to Y1, Y3, Y5, and Y6 (using 14% binder phase content), Y9, Y10, Y11, and Y12 (using 18% binder phase content) and Y2, Y4, Y7, and Y8 (using 24% binder phase content) show significantly improved strength and toughness. However, significantly increasing the binder phase content to improve the strength and toughness of cermet materials is costly and difficult to implement in actual industrial production. Therefore, it is necessary to control the amount of binder phase used to reduce production costs.
[0006] Therefore, it is necessary to provide a high-nitrogen cermet material with a special core-ring structure to improve the wear resistance and impact resistance of Ti(C,N)-based cermet materials while controlling the preparation cost and solving the porosity defects caused by high-nitrogen TiCN raw materials. Summary of the Invention
[0007] The technical problem to be solved by the present invention is to overcome the shortcomings of the prior art and provide a metal ceramic material with a white core and black ring structure that has high hardness, high toughness and excellent impact resistance, as well as its preparation method.
[0008] To solve the above-mentioned technical problems, the present invention adopts the following technical solution.
[0009] A metal-ceramic material with a white core and black ring structure, comprising the following raw materials by mass percentage: Ti(C) 0.3 N 0.7 ) is 10% to 20%, Ti(C) 0.5 N 0.5 The content of the raw materials is 40%–50%, TaC is 1%–4%, WC is 15%–30%, TiWC is 0%–10%, Mo2C is 2%–5%, Cr3C2 is 0.2%–1.2%, and the total content of Co and Ni is 8%–14%. The metal ceramic material also contains carbon powder, and the amount of carbon powder added is 0.35%–1% of the total mass of the raw materials.
[0010] The aforementioned metal-ceramic material, further improved, comprises Ti(C) 0.3 N 0.7 The Fisher particle size of the Ti(C) is 1 μm to 2 μm. 0.5 N 0.5 The Fisher particle size of the following components is 0.5 μm to 2.6 μm: TaC has a Fisher particle size of 1 μm to 2 μm; WC has a Fisher particle size of 0.5 μm to 1 μm; TiWC has a Fisher particle size of 0.5 μm to 4 μm; Mo2C has a Fisher particle size of 1 μm to 2 μm; Cr3C2 has a Fisher particle size of 1 μm to 2 μm; Co has a Fisher particle size of 1 μm to 1.5 μm; and Ni has a Fisher particle size of 2 μm to 2.5 μm. The atomic ratio of Ti to W in TiWC is 0.7 to 1.5.
[0011] The aforementioned metal-ceramic material, further improved, comprises Ti(C) 0.5 N 0.5 The Fisher particle size of the TiWC is 0.5 μm to 0.9 μm, and the Fisher particle size of the TiWC is 0.5 μm to 2.0 μm.
[0012] The aforementioned metal-ceramic material is further improved by comprising a white-core, black-ring phase; in the white-core, black-ring phase, both the white core and the black ring are formed by a (Ti,W,Mo,Ta)(C,N) solid solution; within the same white-core, black-ring phase, the content of C in the white core is greater than that in the black ring, the content of W in the white core is greater than that in the black ring, the content of Mo in the white core is greater than that in the black ring, the content of Ta in the white core is greater than that in the black ring, the content of N in the white core is less than that in the black ring, and the content of Ti in the white core is less than that in the black ring.
[0013] The white-core, black-ring phase of this invention, by atomic percentage, comprises 30.0%–65.0% C, 6.0%–15.0% W, 1.0%–4.0% Mo, 0.8%–1.5% Ta, 5.0%–15.0% N, and 20.0%–35.0% Ti in the white core; and 18.0%–45.0% C, 1.0%–5.0% W, 0.1%–1.3% Mo, 0.3%–0.6% Ta, 15.0%–40.0% N, and 30.0%–55.0% Ti in the black ring.
[0014] As a general technical concept, the present invention also provides a method for preparing the above-mentioned metal-ceramic material with a white core and black ring structure, comprising the following steps: (1) Weigh the required raw materials according to the mass percentage of each raw material in the metal ceramic material, mix them, and ball mill them to obtain a mixed slurry; (2) The mixed slurry is spray-dried to obtain a mixture; (3) The mixture is molded to obtain a pressed blank; (4) The compact is subjected to degreasing, solid-phase sintering and liquid-phase sintering in sequence to obtain a metal ceramic material with a white core and black ring structure.
[0015] The above preparation method is further improved in step (4), wherein the solid-state sintering is as follows: under vacuum conditions, the temperature is raised from 440°C to temperature T1; under an argon atmosphere, the temperature is raised from T1 to 1250°C to 1280°C and held for 0.5h to 1h; the temperature T1 is 1020°C to 1060°C, the total solid-state sintering time is controlled at 3.5h to 4.5h, and the pressure of the argon atmosphere is 2kPa to 5kPa.
[0016] The above preparation method is further improved in step (4), wherein the liquid phase sintering is as follows: under vacuum conditions, the temperature is raised from 1250℃ to 1280℃ to temperature T2 and held for 2h to 4h; under nitrogen atmosphere, the temperature is raised from T2 to temperature T3 and held for 20min to 40min, and then raised from T3 to 1450℃ to 1530℃ and held for 0.5h to 2h; the temperature T2 is 1320℃ to 1380℃, and the temperature T2 < temperature T3 ≤ 1400℃. The total time of liquid phase sintering is controlled between 2.5h and 6.5h, and the pressure of the nitrogen atmosphere is 200Pa to 350Pa.
[0017] The above preparation method is further improved in step (4), wherein the degreasing treatment is: heating from 300℃~310℃ to 440℃ in a hydrogen atmosphere; the degreasing treatment time is controlled at 4h~6h, and the flow rate of the hydrogen atmosphere is 10L / min~50L / min; the degreasing treatment is further improved by the following treatment: heating to 300℃~310℃ within 2h.
[0018] The above preparation method is further improved in step (4), after the liquid phase sintering, the following treatment is also included: vacuum cooling and forced cooling are performed in sequence; the vacuum cooling is: cooling down to 1000℃ under vacuum conditions; the vacuum cooling time is controlled between 5min and 15min; the forced cooling is: cooling down from 1000℃ to room temperature under an argon atmosphere; the forced cooling time is controlled between 10min and 20min.
[0019] In a further improvement to the above preparation method, in step (1), the ball milling time is 48h to 96h, and polyethylene glycol 4000, ethanol and a ball milling rod are added during the ball milling process. The amount of polyethylene glycol added is 4% to 7% of the total mass of the raw materials, and the amount of the ball milling rod added is 5% to 20% of the total mass of the raw materials.
[0020] Compared with the prior art, the advantages of the present invention are as follows: (1) This invention provides a metal-ceramic material with a white core and black ring structure, a) by adding 10% to 20% Ti(C) 0.3 N 0.7 ) and 40%–50% Ti(C 0.5 N 0.5 This not only avoids uncontrollable denitrification caused by excessively high nitrogen content, but also allows Ti(C) to be converted into nitrogen. 0.5 N 0.5 (a) As the main source of core-ring phase formation, it increases the overall wettability between the hard phase and the binder phase, ensuring both increased material hardness and improved toughness; (b) Adding 1%–4% TaC, 15%–30% WC, 0–10% TiWC, 2%–5% Mo2C, and 0.2%–1.2% Cr3C2, the addition of WC and Mo2C can improve the wettability between the hard phase and the binder phase. Furthermore, the solid solution process of W and Mo elements with the TiCN hard phase is the main reason for the formation of gray rings, white cores, and other structures. In other words, the addition of WC and Mo2C improves the wettability of the cermet. The toughness of the material plays a crucial role. By adding TaC, a dense oxide film is formed after the oxygen reaction, which improves the red hardness and thermal shock resistance of the cermet. Adding Cr3C2 inhibits the growth of hard phase grains in the cermet, thereby improving its hardness and wear resistance. Adding TiWC increases the proportion of the white core phase in the cermet, improving its toughness. Furthermore, this white core phase is not formed through sintering, thus effectively controlling its proportion within the cermet microstructure and reducing the uncertainty of white core phase formation through pure sintering. The cermet material of this invention achieves a Vickers hardness of 1641 HV. 30 Its fracture toughness can reach 11.23 MPa.m. 1 / 2 Its flexural strength can reach 2648MPa.
[0021] (2) The metal-ceramic material of the present invention, through optimization of Ti(C) 0.3 N 0.7 The Fisher particle size of Ti(C) is 1μm to 2μm. 0.5 N 0.5The Fisher particle size of Cr3C2 is 0.5μm to 2.6μm, that of TaC is 1μm to 2μm, that of WC is 0.5μm to 1μm, that of TiWC is 0.5μm to 4μm, that of Mo2C is 1μm to 2μm, that of Cr3C2 is 1μm to 2μm, that of Co is 1μm to 1.5μm, and that of Ni is 2μm to 2.5μm. This can achieve the purpose of changing the core-ring phase structure in the cermet material, thereby obtaining a cermet material with high hardness, high toughness and excellent impact resistance. Furthermore, the cermet material of the present invention comprises a white-core, black-ring phase. In the white-core, black-ring phase, both the white core and the black ring are formed by a (Ti,W,Mo,Ta)(C,N) solid solution. The C content in the white core is greater than that in the black ring, the W content in the white core is greater than that in the black ring, the Mo content in the white core is greater than that in the black ring, the Ta content in the white core is greater than that in the black ring, the N content in the white core is less than that in the black ring, and the Ti content in the white core is less than that in the black ring. This special core-ring structure combines high hardness and high toughness, which is beneficial to improving the toughness of the cermet material without significantly affecting the hardness, thereby improving the impact resistance of the material.
[0022] (3) To address the problem of pore defects easily generated inside existing high-nitrogen Ti(C,N)-based cermet materials, this invention creatively proposes a method for preparing cermet materials with a white core and black ring structure. The method involves ball milling, spray drying, molding, degreasing, solid-state sintering, and liquid-state sintering to obtain the cermet material with the white core and black ring structure. In the solid-state sintering stage of this invention, sintering is carried out under vacuum conditions below temperature T1 to remove residual H elements in the sample after degreasing, avoiding adverse effects such as porosity and hydrogen embrittlement caused by H elements in the molded sample; sintering is carried out under an argon atmosphere above temperature T1, which can reduce the volatilization of the binder phase at high temperatures and inhibit the denitrification reaction; simultaneously, the total solid-state sintering time is controlled between 3.5h and 4.5h, which not only eliminates the internal stress of the powder particles but also facilitates solid-state diffusion between raw materials, promoting the formation of the white core phase in the cermet material. In the liquid phase sintering stage of this invention, sintering is carried out under vacuum conditions at temperatures below T2 to improve the wettability between the hard phase and the binder phase, accelerate the rearrangement of hard phase particles, and facilitate the densification process of the sintered body. Sintering is carried out under a nitrogen atmosphere at temperatures above T2. On the one hand, the N2 atmosphere can suppress denitrification of the sintered body, avoiding excessive denitrification reactions that could lead to an overly thick annular phase and surface pores. On the other hand, the micro N2 pressure is insufficient to form a nitriding pressure, preventing the formation of a fine hard phase layer on the sample surface, which could cause differences in the internal and external microstructure of the sample and improve the stability of the material's mechanical properties.
[0023] (4) The preparation method of the present invention adopts a rapid cooling strategy of "vacuum cooling + forced cooling", which can suppress the grain growth process inside the metal ceramic material and avoid the phenomenon of rich binder phase on the sample surface, so as to improve the uniformity of the inner and outer distribution of the binder phase. Attached Figure Description
[0024] Figure 1 This is a SEM image of the metal-ceramic material with a white core and black ring structure obtained in Example 5 of the present invention. Detailed Implementation
[0025] The present invention will be further described below with reference to the accompanying drawings and specific preferred embodiments, but this does not limit the scope of protection of the present invention. All materials and instruments used in the following embodiments are commercially available.
[0026] Example 1: A metal-ceramic material with a white core and black ring structure according to the present invention comprises, by mass percentage, the following raw materials: Ti(C) 0.3 N 0.7 ) is 16%, Ti(C) 0.5 N 0.5 The composition of the cermet material is as follows: TiWC (Ti / W = 1.2 at%), (Ti+W) / C = 1 at%), Mo2C (4%), Cr3C2 (1%), Co (8.05%), and Ni (3.95%). Carbon powder is also added to this cermet material. 0.3 N 0.7 ), Ti(C 0.5 N 0.5 The total mass of Ti(C), TaC, WC, TiWC, Mo2C, Cr3C2, Co, and Ni is 0.45%. Among them, Ti(C) 0.3 N 0.7 The powder has a Fisher particle size of 1.6 μm, and the Ti(C) powder has a particle size of 1.6 μm. 0.5 N 0.5 The Fisher particle size of the powders is 1.22 μm, the Fisher particle size of TaC powder is 1.12 μm, the Fisher particle size of WC powder is 0.75 μm, the Fisher particle size of TiWC powder is 3.82 μm, the Fisher particle size of Mo2C powder is 1.49 μm, the Fisher particle size of Cr3C2 powder is 1.48 μm, the Fisher particle size of Co powder is 1.28 μm, and the Fisher particle size of Ni powder is 2.28 μm.
[0027] The method for preparing the metal-ceramic material with a white core and black ring structure in this embodiment includes the following steps: (1) Weigh the required raw materials according to the mass percentage of each raw material in the above metal ceramic material and add them to the ball mill barrel; then, add polyethylene glycol 4000 (PEG4000), industrial ethanol and ball milling rod. The amount of polyethylene glycol 4000 added is 4% of the total mass of the raw materials and the amount of ball milling rod added is 15% of the total mass of the raw materials. Ball mill for 50 hours to obtain a mixed slurry.
[0028] (2) The above mixture slurry is spray-dried to obtain a mixture.
[0029] (3) The above mixture is molded into a compact.
[0030] (4) Degreasing and sintering (4.1) Place the above-mentioned pressed blank in a sintering furnace and raise the temperature from room temperature to 310°C within 2 hours; under a hydrogen atmosphere (H2 flow rate of 30L / min), raise the temperature to 440°C within 5 hours for degreasing treatment.
[0031] (4.2) Subsequently, under vacuum conditions, the temperature was increased from 440℃ to 1025℃ in 1.40h; then under argon atmosphere (5kPa), the temperature was increased from 1025℃ to 1270℃ in 1.60h, and held at 1270℃ for 1h to carry out solid-state sintering.
[0032] (4.3) Then, under vacuum conditions, the temperature is increased from 1270℃ to 1330℃ in 20 min and held at 1330℃ for 2 h; under nitrogen atmosphere (200 Pa), the temperature is increased from 1330℃ to 1400℃ in 20 min and held at 1400℃ for 20 min, and then increased from 1400℃ to 1510℃ in 30 min and held at 1510℃ for 2 h to carry out liquid phase sintering.
[0033] (4.4) Finally, under vacuum conditions, the temperature was reduced from 1510℃ to 1000℃ in 15 minutes for vacuum cooling; under argon atmosphere, the temperature was reduced from 1000℃ to room temperature in 20 minutes for forced cooling, to obtain a metal ceramic material with a white core and black ring structure.
[0034] The cermet material of this embodiment comprises a white-core black-ring phase, a black-core gray-ring phase, a white-core gray-ring phase, and a binder phase. In the white-core black-ring phase, both the white core and the black rings are formed by a (Ti,W,Mo,Ta)(C,N) solid solution. The C content in the white core is greater than that in the black rings, the W content in the white core is greater than that in the black rings, the Mo content in the white core is greater than that in the black rings, the Ta content in the white core is greater than that in the black rings, the N content in the white core is less than that in the black rings, and the Ti content in the white core is less than that in the black rings.
[0035] The metallographic and mechanical properties of the cermet material obtained in this embodiment were tested. The metallographic identification result was A02B00; its Vickers hardness reached 1582 HV. 30 The fracture toughness is 8.07 MPa.m. 1 / 2 The bending strength is 1753 MPa. Metallographic analysis results show that Class A porosity represents a size below 10 μm, and Class B porosity represents a size of 10-25 μm. The numbers 00, 02, 04, 06, and 08 following A and B indicate the volume content in the most severe field of view as 0, 0.02%, 0.06%, 0.2%, and 0.6%, respectively.
[0036] Example 2: A metal-ceramic material with a white core and black ring structure according to the present invention comprises, by mass percentage, the following raw materials: Ti(C) 0.3 N 0.7 ) is 16%, Ti(C) 0.5 N 0.5 The composition of the cermet material is as follows: TiWC (Ti / W = 1.2 at%), (Ti+W) / C = 1 at%), Mo2C (4%), Cr3C2 (1%), Co (8.05%), and Ni (3.95%). Carbon powder is also added to this cermet material. 0.3 N 0.7 ), Ti(C 0.5 N 0.5 The total mass of Ti(C), TaC, WC, TiWC, Mo2C, Cr3C2, Co, and Ni is 0.45%. Among them, Ti(C) 0.3 N 0.7 The powder has a Fisher particle size of 1.6 μm, and the Ti(C) powder has a particle size of 1.6 μm. 0.5 N 0.5 The Fisher particle size of the powders is 2.58 μm, the Fisher particle size of TaC powder is 1.12 μm, the Fisher particle size of WC powder is 0.75 μm, the Fisher particle size of TiWC powder is 3.82 μm, the Fisher particle size of Mo2C powder is 1.49 μm, the Fisher particle size of Cr3C2 powder is 1.48 μm, the Fisher particle size of Co powder is 1.28 μm, and the Fisher particle size of Ni powder is 2.28 μm.
[0037] The preparation method of the metal-ceramic material with a white core and black ring structure in this embodiment is basically the same as the preparation method of the metal-ceramic material with a white core and black ring structure in Example 1, the only difference being that the raw materials of the metal-ceramic material are different.
[0038] The cermet material of this embodiment comprises a white-core black-ring phase, a black-core gray-ring phase, a white-core gray-ring phase, and a binder phase. In the white-core black-ring phase, both the white core and the black rings are formed by a (Ti,W,Mo,Ta)(C,N) solid solution. The C content in the white core is greater than that in the black rings, the W content in the white core is greater than that in the black rings, the Mo content in the white core is greater than that in the black rings, the Ta content in the white core is greater than that in the black rings, the N content in the white core is less than that in the black rings, and the Ti content in the white core is less than that in the black rings.
[0039] The metal-ceramic material prepared in this embodiment has the following metallographic identification result: A02B00; its Vickers hardness can reach 1550 HV. 30 The fracture toughness is 7.97 MPa.m. 1 / 2 Its flexural strength is 1357 MPa.
[0040] Example 3: A metal-ceramic material with a white core and black ring structure according to the present invention comprises, by mass percentage, the following raw materials: Ti(C) 0.3 N 0.7 ) is 16%, Ti(C) 0.5 N 0.5 The composition of the cermet material is as follows: TiWC (Ti / W = 1.2 at%), (Ti+W) / C = 1 at%), Mo2C (4%), Cr3C2 (1%), Co (8.05%), and Ni (3.95%). Carbon powder is also added to this cermet material. 0.3 N 0.7 ), Ti(C 0.5 N 0.5 The total mass of Ti(C), TaC, WC, TiWC, Mo2C, Cr3C2, Co, and Ni is 0.45%. Among them, Ti(C) 0.3 N 0.7 The powder has a Fisher particle size of 1.6 μm, and the Ti(C) powder has a particle size of 1.6 μm. 0.5 N 0.5 The Fisher particle size of the powders is 1.22 μm, the Fisher particle size of TaC powder is 1.12 μm, the Fisher particle size of WC powder is 0.75 μm, the Fisher particle size of TiWC powder is 1.78 μm, the Fisher particle size of Mo2C powder is 1.49 μm, the Fisher particle size of Cr3C2 powder is 1.48 μm, the Fisher particle size of Co powder is 1.28 μm, and the Fisher particle size of Ni powder is 2.28 μm.
[0041] The preparation method of the metal-ceramic material with a white core and black ring structure in this embodiment is basically the same as the preparation method of the metal-ceramic material with a white core and black ring structure in Example 1, the only difference being that the raw materials of the metal-ceramic material are different.
[0042] The cermet material of this embodiment comprises a white-core black-ring phase, a black-core gray-ring phase, a white-core gray-ring phase, and a binder phase. In the white-core black-ring phase, both the white core and the black rings are formed by a (Ti,W,Mo,Ta)(C,N) solid solution. The C content in the white core is greater than that in the black rings, the W content in the white core is greater than that in the black rings, the Mo content in the white core is greater than that in the black rings, the Ta content in the white core is greater than that in the black rings, the N content in the white core is less than that in the black rings, and the Ti content in the white core is less than that in the black rings.
[0043] The metal-ceramic material prepared in this embodiment has the following metallographic identification result: A02B00; its Vickers hardness can reach 1593HV. 30 The fracture toughness is 8.67 MPa.m. 1 / 2 Its flexural strength is 1828 MPa.
[0044] Example 4: A metal-ceramic material with a white core and black ring structure according to the present invention comprises, by mass percentage, the following raw materials: Ti(C) 0.3 N 0.7 ) is 16%, Ti(C) 0.5 N 0.5 The composition of the cermet material is as follows: TiWC (Ti / W = 1.2 at%), (Ti+W) / C = 1 at%), Mo2C (4%), Cr3C2 (1%), Co (8.05%), and Ni (3.95%). Carbon powder is also added to this cermet material. 0.3 N 0.7 ), Ti(C 0.5 N 0.5 The total mass of Ti(C), TaC, WC, TiWC, Mo2C, Cr3C2, Co, and Ni is 0.45%. Among them, Ti(C) 0.3 N 0.7 The powder has a Fisher particle size of 1.6 μm, and the Ti(C) powder has a particle size of 1.6 μm. 0.5 N 0.5The Fisher particle size of the powders is 0.97 μm, the Fisher particle size of TaC powder is 1.12 μm, the Fisher particle size of WC powder is 0.75 μm, the Fisher particle size of TiWC powder is 1.78 μm, the Fisher particle size of Mo2C powder is 1.49 μm, the Fisher particle size of Cr3C2 powder is 1.48 μm, the Fisher particle size of Co powder is 1.28 μm, and the Fisher particle size of Ni powder is 2.28 μm.
[0045] The preparation method of the metal-ceramic material with a white core and black ring structure in this embodiment is basically the same as the preparation method of the metal-ceramic material with a white core and black ring structure in Example 1, the only difference being that the raw materials of the metal-ceramic material are different.
[0046] The cermet material of this embodiment comprises a white-core black-ring phase, a black-core gray-ring phase, a white-core gray-ring phase, and a binder phase. In the white-core black-ring phase, both the white core and the black rings are formed by a (Ti,W,Mo,Ta)(C,N) solid solution. The C content in the white core is greater than that in the black rings, the W content in the white core is greater than that in the black rings, the Mo content in the white core is greater than that in the black rings, the Ta content in the white core is greater than that in the black rings, the N content in the white core is less than that in the black rings, and the Ti content in the white core is less than that in the black rings.
[0047] The metal-ceramic material prepared in this embodiment has the following metallographic identification result: A02B00; its Vickers hardness can reach 1605HV. 30 The fracture toughness is 8.63 MPa.m. 1 / 2 Its flexural strength is 1872 MPa.
[0048] Example 5: A metal-ceramic material with a white core and black ring structure according to the present invention comprises, by mass percentage, the following raw materials: Ti(C) 0.3 N 0.7 ) is 16%, Ti(C) 0.5 N 0.5 The composition of the cermet material is as follows: TiWC (Ti / W = 1.2 at%), (Ti+W) / C = 1 at%), Mo2C (4%), Cr3C2 (1%), Co (8.05%), and Ni (3.95%). Carbon powder is also added to this cermet material. 0.3 N 0.7 ), Ti(C 0.5 N 0.5 The total mass of Ti(C), TaC, WC, TiWC, Mo2C, Cr3C2, Co, and Ni is 0.45%. Among them, Ti(C) 0.3 N0.7 The powder has a Fisher particle size of 1.6 μm, and the Ti(C) powder has a particle size of 1.6 μm. 0.5 N 0.5 The Fisher particle size of the powders is 0.80 μm, the Fisher particle size of TaC powder is 1.12 μm, the Fisher particle size of WC powder is 0.75 μm, the Fisher particle size of TiWC powder is 1.78 μm, the Fisher particle size of Mo2C powder is 1.49 μm, the Fisher particle size of Cr3C2 powder is 1.48 μm, the Fisher particle size of Co powder is 1.28 μm, and the Fisher particle size of Ni powder is 2.28 μm.
[0049] The preparation method of the metal-ceramic material with a white core and black ring structure in this embodiment is basically the same as the preparation method of the metal-ceramic material with a white core and black ring structure in Example 1, the only difference being that the raw materials of the metal-ceramic material are different.
[0050] Figure 1 This is a SEM image of the metal-ceramic material with a white core and black ring structure obtained in Example 5 of the present invention. Figure 1 In the diagram, the red arrow points to the white-core, black-ring phase. (From...) Figure 1 As can be seen, the cermet material of this embodiment contains relatively fine black-core gray-ring phases, white-core black-ring phases (indicated by red arrows), a small amount of white-core gray-ring phases, and a small amount of binder phase aggregation regions. In the white-core black-ring phase, both the white core and the black ring are formed by (Ti,W,Mo,Ta)(C,N) solid solutions. The C content in the white core is greater than that in the black ring, the W content in the white core is greater than that in the black ring, the Mo content in the white core is greater than that in the black ring, the Ta content in the white core is greater than that in the black ring, the N content in the white core is less than that in the black ring, and the Ti content in the white core is less than that in the black ring.
[0051] The metal-ceramic material prepared in this embodiment has the following metallographic identification result: A02B00; its Vickers hardness can reach 1641 HV. 30 The fracture toughness is 11.23 MPa.m. 1 / 2 Its flexural strength is 2648 MPa. Comparative Example 1: A metal-ceramic material, by mass percentage, comprises the following raw materials: Ti(C) 0.3 N 0.7 ) is 24%, Ti(C) 0.5 N 0.5 The composition of the cermet material is as follows: Ti(C) = 32%, TaC = 2%, WC = 18%, TiWC = 7%, Mo2C = 4%, Cr3C2 = 1%, Co = 8.05%, and Ni = 3.95%. Carbon powder is also added to this cermet material, with the amount of carbon powder added being equal to the amount of Ti(C). 0.3 N0.7 ), Ti(C 0.5 N 0.5 The total mass of Ti(C), TaC, WC, TiWC, Mo2C, Cr3C2, Co, and Ni is 0.45%. Among them, Ti(C) 0.3 N 0.7 The powder has a Fisher particle size of 1.6 μm, and the Ti(C) powder has a particle size of 1.6 μm. 0.5 N 0.5 The Fisher particle size of the powders is 1.20 μm, the Fisher particle size of TaC powder is 1.12 μm, the Fisher particle size of WC powder is 0.75 μm, the Fisher particle size of TiWC powder is 1.78 μm, the Fisher particle size of Mo2C powder is 1.49 μm, the Fisher particle size of Cr3C2 powder is 1.48 μm, the Fisher particle size of Co powder is 1.28 μm, and the Fisher particle size of Ni powder is 2.28 μm.
[0052] The preparation method of the comparative metal-ceramic material is basically the same as that of the metal-ceramic material with white core and black ring structure in Example 1, the only difference being that the raw materials of the metal-ceramic materials are different.
[0053] The metallographic identification result of the metal-ceramic material prepared in this comparative example is: A04B04; its Vickers hardness is 1580 HV. 30 The fracture toughness is 7.76 MPa.m. 1 / 2 Its flexural strength is 733 MPa.
[0054] Comparative Example 2: A metal-ceramic material whose raw materials are the same as those of the metal-ceramic material with a white core and black ring structure in Example 5.
[0055] The preparation method of this metal-ceramic material includes the following steps: (1) Weigh the required raw materials according to the mass percentage of each raw material in the above metal ceramic material and add them to the ball mill barrel; then, add polyethylene glycol 4000 (PEG4000), industrial ethanol and ball milling rod. The amount of polyethylene glycol 4000 added is 4% of the total mass of the raw materials, and the amount of ball milling rod added is 15% of the total mass of the raw materials. Ball mill for 50 hours to obtain a mixed slurry.
[0056] (2) The above mixture slurry is spray-dried to obtain a mixture.
[0057] (3) The above mixture is molded into a compact.
[0058] (4) Degreasing and sintering (4.1) Place the above-mentioned pressed blank in a sintering furnace and raise the temperature from room temperature to 310°C within 2 hours; under a hydrogen atmosphere (H2 flow rate of 30L / min), raise the temperature to 440°C within 5 hours for degreasing treatment.
[0059] (4.2) Subsequently, under vacuum conditions, the temperature was raised from 440℃ to 1150℃ in 1.40h; then under nitrogen atmosphere (100Pa), the temperature was raised from 1150℃ to 1320℃ in 1.60h, and held at 1320℃ for 1.25h for solid-state sintering.
[0060] (4.3) Then, under vacuum conditions, the temperature is increased from 1320℃ to 1330℃ in 20 min and held at 1330℃ for 40 min; under nitrogen atmosphere (200 Pa), the temperature is increased from 1330℃ to 1400℃ in 20 min and held at 1400℃ for 20 min, and then increased from 1400℃ to 1510℃ in 30 min and held at 1510℃ for 2 h to carry out liquid phase sintering.
[0061] (4.4) Finally, under vacuum conditions, the temperature was reduced from 1510℃ to 1000℃ in 15 minutes for vacuum cooling; under argon atmosphere, the temperature was reduced from 1000℃ to room temperature in 30 minutes for forced cooling to obtain the metal ceramic material.
[0062] The metallographic identification result of the metal-ceramic material prepared in this comparative example is: A02B08; its Vickers hardness reaches 1569 HV. 30 The fracture toughness is 7.31 MPa.m. 1 / 2 Its flexural strength is 1079 MPa.
[0063] Comparative Example 3: A metal-ceramic material whose raw materials are the same as those of the metal-ceramic material with a white core and black ring structure in Example 5.
[0064] The preparation method of this metal ceramic material is basically the same as the preparation method of the metal ceramic material with white core and black ring structure in Example 5. The only difference is that in step (4.3), the entire liquid phase sintering process is carried out under vacuum conditions.
[0065] The metallographic identification result of the metal-ceramic material prepared in this comparative example is: A02B08; its Vickers hardness reaches 1537 HV. 30 The fracture toughness is 8.69 MPa.m. 1 / 2 Its flexural strength is 1112 MPa.
[0066] Table 1 Performance test results of metal-ceramic materials
[0067] As shown in Table 1, the cermet materials prepared in Examples 1 to 5 did not undergo uncontrollable denitrification reactions and all exhibited good density, thus demonstrating high hardness, high toughness, and excellent impact resistance. Among them, Example 5, due to the main raw material Ti(C)… 0.5 N 0.5 The TiWC particles were the finest in Examples 1-5, exhibiting significant grain-refining strengthening effects, thus achieving the best hardness, strength, and impact resistance. In contrast, the cermet materials prepared in Comparative Examples 1-3, due to the excessive addition of high-nitrogen TiCN raw materials and changes in the sintering process, resulted in a less dense cermet microstructure with obvious porosity, and their impact resistance was not ideal, showing significant performance degradation.
[0068] The above description is merely a preferred embodiment of the present invention and is not intended to limit the present invention in any way. Although the present invention has been disclosed above with reference to preferred embodiments, it is not intended to limit the present invention. Any person skilled in the art can make many possible variations and modifications to the technical solutions of the present invention using the methods and techniques disclosed above, or modify them into equivalent embodiments with equivalent changes, without departing from the spirit and technical essence of the present invention. Therefore, any simple modifications, equivalent substitutions, equivalent changes, and modifications made to the above embodiments based on the technical essence of the present invention without departing from the content of the technical solutions of the present invention shall still fall within the protection scope of the technical solutions of the present invention.
Claims
1. A metal-ceramic material with a white core and black ring structure, characterized in that, By mass percentage, it contains the following raw materials: Ti(C) 0.3 N 0.7 ) is 10% to 20%, Ti(C) 0.5 N 0.5 The content of the raw materials is 40%–50%, TaC is 1%–4%, WC is 15%–30%, TiWC is 0%–10%, Mo2C is 2%–5%, Cr3C2 is 0.2%–1.2%, and the total content of Co and Ni is 8%–14%. The metal ceramic material also contains carbon powder, and the amount of carbon powder added is 0.35%–1% of the total mass of the raw materials.
2. The metal-ceramic material with a white core and black ring structure according to claim 1, characterized in that, The Ti(C) 0.3 N 0.7 The Fisher particle size of the Ti(C) is 1 μm to 2 μm. 0.5 N 0.5 The Fisher particle size of the following components is 0.5 μm to 2.6 μm: TaC has a Fisher particle size of 1 μm to 2 μm; WC has a Fisher particle size of 0.5 μm to 1 μm; TiWC has a Fisher particle size of 0.5 μm to 4 μm; Mo2C has a Fisher particle size of 1 μm to 2 μm; Cr3C2 has a Fisher particle size of 1 μm to 2 μm; Co has a Fisher particle size of 1 μm to 1.5 μm; and Ni has a Fisher particle size of 2 μm to 2.5 μm. The atomic ratio of Ti to W in TiWC is 0.7 to 1.
5.
3. The metal-ceramic material with a white core and black ring structure according to claim 2, characterized in that, The Ti(C) 0.5 N 0.5 The Fisher particle size of the TiWC is 0.5 μm to 0.9 μm, and the Fisher particle size of the TiWC is 0.5 μm to 2.0 μm.
4. The metal-ceramic material with a white core and black ring structure according to any one of claims 1 to 3, characterized in that, The metal-ceramic material comprises a white-core, black-ring phase; in the white-core, black-ring phase, both the white core and the black ring are formed by a (Ti,W,Mo,Ta)(C,N) solid solution; within the same white-core, black-ring phase, the C content in the white core is greater than that in the black ring, the W content in the white core is greater than that in the black ring, the Mo content in the white core is greater than that in the black ring, the Ta content in the white core is greater than that in the black ring, the N content in the white core is less than that in the black ring, and the Ti content in the white core is less than that in the black ring.
5. A method for preparing a metal-ceramic material with a white core and black ring structure as described in any one of claims 1 to 4, characterized in that, Includes the following steps: (1) Weigh the required raw materials according to the mass percentage of each raw material in the metal ceramic material, mix them, and ball mill them to obtain a mixed slurry; (2) The mixed slurry is spray-dried to obtain a mixture; (3) The mixture is molded to obtain a pressed blank; (4) The compact is subjected to degreasing, solid-phase sintering and liquid-phase sintering in sequence to obtain a metal ceramic material with a white core and black ring structure.
6. The method for preparing the metal-ceramic material with a white core and black ring structure according to claim 5, characterized in that, In step (4), the solid-state sintering is as follows: under vacuum conditions, the temperature is raised from 440℃ to temperature T1; under an argon atmosphere, the temperature is raised from T1 to 1250℃~1280℃ and held for 0.5h~1h; the temperature T1 is 1020℃~1060℃, the total solid-state sintering time is controlled at 3.5h~4.5h, and the pressure of the argon atmosphere is 2kPa~5kPa.
7. The method for preparing a metal-ceramic material with a white core and black ring structure according to claim 6, characterized in that, In step (4), the liquid phase sintering is as follows: under vacuum conditions, the temperature is raised from 1250℃ to 1280℃ to temperature T2 and held for 2h to 4h; under nitrogen atmosphere, the temperature is raised from T2 to temperature T3 and held for 20min to 40min, and then raised from T3 to 1450℃ to 1530℃ and held for 0.5h to 2h; the temperature T2 is 1320℃ to 1380℃, and the temperature T2 < temperature T3 ≤ 1400℃. The total time of the liquid phase sintering is controlled between 2.5h and 6.5h, and the pressure of the nitrogen atmosphere is 200Pa to 350Pa.
8. The method for preparing a metal-ceramic material with a white core and black ring structure according to any one of claims 5 to 7, characterized in that, In step (4), the degreasing treatment is as follows: under a hydrogen atmosphere, the temperature is raised from 300℃~310℃ to 440℃; the time of the degreasing treatment is controlled within 4h~6h, and the flow rate of the hydrogen atmosphere is 10L / min~50L / min; before the degreasing treatment, the following treatment is also included: the temperature is raised to 300℃~310℃ within 2h.
9. The method for preparing a metal-ceramic material with a white core and black ring structure according to any one of claims 5 to 7, characterized in that, In step (4), after the liquid phase sintering, the following treatment is also included: vacuum cooling and forced cooling are performed in sequence; the vacuum cooling is: cooling down to 1000℃ under vacuum conditions; the vacuum cooling time is controlled between 5min and 15min; the forced cooling is: cooling down from 1000℃ to room temperature under an argon atmosphere; the forced cooling time is controlled between 10min and 20min.
10. A method for preparing a metal-ceramic material with a white core and black ring structure according to any one of claims 5 to 7, characterized in that, In step (1), the ball milling time is 48h to 96h. During the ball milling process, polyethylene glycol 4000, ethanol and a ball milling rod are added. The amount of polyethylene glycol added is 4% to 7% of the total mass of the raw materials, and the amount of the ball milling rod added is 5% to 20% of the total mass of the raw materials.
Citation Information
Patent Citations
Nanoparticle interface reinforced Ti(C, N)-based metal ceramic material with high nitrogen content and preparation method thereof
CN111378888A
Mixed crystal Ti (C, N)-based metal ceramic material and preparation method thereof
CN113025861A